Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas VI SDN Tompu Kecamatan Sigi Biromaru - Rizal, Rizal; Husain, Sarjan N.; Saehana, Sahrul (Mitra Sains, 2016)
The research was conducted on a semester at SDN Tompu Biromaru Sigi District of school year 2014-2015. Problems in the study was whether the application of Jigsaw cooperative learning model can improve the activity and results of the sixth grade students learn science SDN Tompu District of Sigi Biromaru. The method used is a cyclic method at class action research with two cycles. Each cycle consists of two meetings results showed that the application of cooperative learning model Jigsaw shown to enhance the activity and the results of learning science in grade VI SDN Tompu Biromaru Sigi District of criteria that are in the category of fairly to very good. While the magnitude of the increase in student learning outcomes cycle I were in the medium category and second cycle were in the high category. Thus, it was concluded that the application of Jigsaw cooperative learning model can improve the activity and the results of the sixth grade students learn science SDN Tompu District of Sigi Biromaru.